The situation of Modified Electroconvulsive Therapy in psychiatric patients in Galya Rajanagarindra Institute - สกุลพันธุ์ สุพัตรา; สุวรรณรงค์ กลิ่นชบา; ถาน้อย วารีรัตน์ (Journal of The Royal Thai Army Nurses, 2019)
The present study aimed to identify the situations of the modified electroconvulsive therapy in psychiatric patients, investigating the relationship and predictive power of the factors predicting adverse effect and complications of the modified electroconvulsive therapy in psychiatric patients. The study sample consisted of 175 psychiatric patients received modified electroconvulsive therapy. Data were collected by using demographic data, history illness, information relating to electrical therapy, adverse effect and complications data of Modified Electroconvulsive Therapy in psychiatric patients. Data were analyzed using descriptive analysis, chi-square test and logistic regression. The study found that most of the patients were 62.3 % male, 29.2 % had body mass index ≥ 25 (overweight or obese). 72 % of psychiatric patients were diagnosed in schizophrenia. 42.3 % had comorbidity. Body Mass Index (BMI) and Clozapine treatment were positively significant correlated with the adverse effects and complications of the modified electroconvulsive therapy at the .05 level. Non-responding to medical treatment was significant correlated with the adverse effects and complications of the modified electroconvulsive therapy at the .01 level. Result found that the BMI level more than 30 can predict the adverse effects and complications of the modified electroconvulsive therapy at the .01 level. The variance expand of this predictive factor was 18.9 Findings from this study could be used as a foundation for nursing planning in reducing the adverse effects and complications from the Modified Electroconvulsive Therapy in psychiatric patients, especially overweight or obese patients receiving clozapine and patients not responding to therapy. Therefore, nurses should develop the nursing practice guidelines for overweight or obese patients treated with modified electroconvulsive therapy to reduce the adverse effects or complications of the modified electroconvulsive therapy.